KOMODIFIKASI PERNIKAHAN “ MENUJU JANJI SUCI “ DI TRANS TV - Enga, Anastasia H.P (Interaksi: Jurnal Ilmu Komunikasi, 2016)
AbstractCommodification or the transformation process of goods and services are valued for their use, into a commodity that is valued for what they can get in the market, such as commercial agriculture to sell food, produce drama for commercial broadcasting. Marriage celebrities homelands is now a mass produced product with a variety of packing with the aim of a variety of interests and tastes of the market. So now the wedding of the artists as wellas more general topics that can be commercialized in any form of mass media to increase profits. Trans tv no longer pay attention to the publik frequency, use valuas taken here replaced by the exchange rate, the sanctity of the wedding pair of human children have been used a business area for the media konglmerasi to benefit is not small. Keywords:  commodification, wedding artists, television